1993
DOI: 10.1111/j.1365-2672.1993.tb03009.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the detection of thermotolerant campylobacters in foods: results of an inter‐laboratory study

Abstract: An inter‐laboratory comparison of three methods for the detection of thermotolerant campylobacters is described. One of two proposed by the International Standards Organisation was significantly better for detecting campylobacters in minced chicken skin naturally contaminated at levels of either 2 or 10 cells per 10 g, but involved extensive manipulations not likely to be well received in a busy laboratory. This method yielded 18% false negative results compared with 48–54% for the other two but also gave 8% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Although significant, there was evidence that the two methods deviated, with some samples having differences of up to 690 MPN/L. However, a single study by Scotter et al ( 1993 ), demonstrated that even with the use of three independent culture-based methods (two of which were international standards) on the same sample, inter-laboratory Campylobacter results correlated, at most, 42%. Thus, it can be assumed that the results of the sensitivity, specificity and diagnostic accuracy, achieved for AS/NZS during the current study, is indicative of the normal variation observed in culture-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant, there was evidence that the two methods deviated, with some samples having differences of up to 690 MPN/L. However, a single study by Scotter et al ( 1993 ), demonstrated that even with the use of three independent culture-based methods (two of which were international standards) on the same sample, inter-laboratory Campylobacter results correlated, at most, 42%. Thus, it can be assumed that the results of the sensitivity, specificity and diagnostic accuracy, achieved for AS/NZS during the current study, is indicative of the normal variation observed in culture-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability to recover injured cells was not assessed, although the author acknowledged that this warranted further investigation. Furthermore, this medium was incubated directly at 42 °C for 24 h, unlike the media used in the present study which were all pre‐incubated at 37 °C for 4 h, a technique shown to improve recovery (Humphrey 1986b, 1989; Scotter et al . 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In a multilaboratory collaborative study, Scotter et al (1993) found that preenrichment of poultry skin samples with a gradual addition of antibiotics Downloaded by [Purdue University] at 14:28 13 April 2015 suppressed competing organisms resulting in an improved recovery of Campylobacter, as did a nonselective blood agar isolation medium used in combination with a membrane filtration technique. Murphy et al (2005) found that the extent to which C. jejuni survived acid stress at pH 4.5 was dependent on the identity of the broth used to culture and stress the cells.…”
Section: Isolation Of Campylobacters From Foodsmentioning
confidence: 98%